Pelatihan Pemahaman dan Pelantunan Syair Tari Pho Berbasis Kearifan Lokal untuk Penguatan Karakter Mahasiswa Program Studi Pendidikan Sendratasik - Yeni Zuryaningsih; Yuli Astuti; Ilham Septian; Samsuri Samsuri (Lembaga Pengembangan Kinerja Dosen, 2026)
Traditional Aceh dance learning in the Sendratasik Education Study Program, Faculty of Teacher Training and Education, Syiah Kuala University, has primarily emphasized mastery of dance movements, while the understanding and recitation of dance lyrics have received less attention. As a result, some students experience difficulties in pronouncing lyrics correctly, interpreting their meanings, and performing confidently. This community service activity aimed to enhance students’ ability to understand, recite, and apply the character values and cultural concepts contained in the Pho Dance lyrics. The program involved 30 students from the 2023, 2024, and 2025 cohorts and employed a peer tutoring method combined with the Experiential Learning model through the stages of Concrete Experience, Reflective Observation, and Abstract Conceptualization. The results showed significant improvements in students’ lyric recitation skills, including pronunciation accuracy, intonation (geureunek), mastery of the South Aceh dialect, and the ability to convey meaning through movement and expression. Students also demonstrated greater confidence during performances and gained a deeper understanding of character values such as politeness, patriotism, mutual respect, affection, and responsibility. Furthermore, they developed broader insights into Acehnese cultural concepts, including peumulia jamee, wedding traditions, religious values, heroism, cultural identity, and cultural preservation. The activity also strengthened cooperation, empathy, and mutual respect among participants, indicating the effectiveness of peer tutoring and Experiential Learning in preserving Acehnese cultural heritage.